Strategi Guru Agama Hindu dalam Menumbuhkan Karakter Siswa Berbasis Ajaran Tri Kaya Parisudha di SDN 14 Pedungan - Trisnawati, Ni Made (Samsara Institute Publisher, 2025)
Character education is an integral part of schooling, particularly through Hindu Religious Education which is rich in moral and ethical teachings. This study aims to describe and analyze the strategies employed by Hindu religion teachers in fostering student character based on the Tri Kaya Parisudha teachings at SDN 14 Pedungan. A descriptive qualitative approach was used, with data collected through observation, in-depth interviews, and documentation. The results show that the teacher implemented various strategies, such as integrating the values of Tri Kaya Parisudha (right thinking, right speech, and right action) into the learning process, habituation through daily religious activities, and character development through role modeling and personal approaches. These strategies proved effective in nurturing students’ religious, honest, disciplined, and responsible character. This study highlights the crucial role of teachers as role models and facilitators in shaping students’ character through contextual and value-based religious approaches.